The Mechanical Characteristics of the Neck Zone for a PEMFC Stack - Zhen Zhang; Fen Zhou; Zhigang Zhan; Jinting Tan; Mu Pan (Energies, 2023)
Generally, the unit cell in a proton exchange membrane fuel cell (PEMFC) stack is divided into different zones according to the characteristics of the bipolar plate. There is a zone that has been neglected, which we define as the “neck zone” for the first time in this work. Uneven stress and deformation are prone to appearing in the neck zone due to its unique structure. A three-dimensional finite element model was applied to study the influence of the membrane electrode assembly (MEA) frame materials on the mechanical characteristics of the neck zone. In addition, the sealing and the water–gas transport performances of the neck zone were evaluated via the stress fluctuation and deformation. It was found that even with the commercial polyethylene naphthalate (PEN) frame, a leak point would be generated at the region with the lowest stress, reducing the performance and even causing safety hazards. The invasion rate was proposed to assess the water–gas transport ability. When an inappropriate frame material was adopted, the invasion rate went up to 32.4%, severely hindering the water and the air transport. It was concluded that MEA frames with a higher elastic modulus and thickness are preferred for the neck zone to obtain a high property of sealing and water–gas transport.